2016
DOI: 10.2139/ssrn.2714238
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Effectiveness of Anti-Cartel Interventions: A Conceptual Framework

Abstract: This paper develops a model of the birth and death of cartels in the presence of enforcement activities by a Competition Authority (CA). We distinguish three sets of interventions: (a) detecting, prosecuting and penalising cartels; (b) actions that aim to stop cartel activity in the short-term, immediately following successful prosecution; (c) actions that aim to prevent the re-emergence of prosecuted cartels in the longer term. The last two intervention activities have not been analysed in the existing litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This result feeds directly into the assumptions employed in this current paper on the sampling differentials, as will be seen in Section III.B. The other, Katsoulacos et al (2016), shares the same conceptual objective as ours, but its approach is very different in at least two respects. First it abstracts from any heterogeneity among cartels, and thereby sidesteps the key issue of selection bias.…”
Section: European Commission Dg Competitionmentioning
confidence: 58%
“…This result feeds directly into the assumptions employed in this current paper on the sampling differentials, as will be seen in Section III.B. The other, Katsoulacos et al (2016), shares the same conceptual objective as ours, but its approach is very different in at least two respects. First it abstracts from any heterogeneity among cartels, and thereby sidesteps the key issue of selection bias.…”
Section: European Commission Dg Competitionmentioning
confidence: 58%
“…Davies and Ormosi (2013) and Davies et al (2018) use simulations to estimate a quantification of harm deterred by antitrust policies, taking into account potential sample selection bias. Based on Harrington and Chang (2009), Katsoulacos et al (2016) develop a framework for evaluating the effects of policy instruments on welfare, simulating different intervention variables and allowing for repeat offenders. Gärtner (2022) uses MC simulations to show the existence of a preemptive push into leniency application (Harrington (2013)).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using a model of birth-and-death and focusing on recidivist cartels, Katsoulacos et al (2016) found that the unmeasured effect is between 1.5 and 2.9 times as large as the detection effect.…”
Section: Literature Reviewmentioning
confidence: 99%